2018
DOI: 10.1007/s13346-018-0510-z
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera standardised aqueous leaf extract-loaded hydrocolloid film dressing: in vivo dermal safety and wound healing evaluation in STZ/HFD diabetic rat model

Abstract: Previously, Moringa oleifera leaf (MOL) standardised aqueous extract-loaded films were successfully developed and they showed potential wound healing activity in vitro. The objective of this study was to evaluate in vivo dermal safety as well as wound healing efficacy of these MOL film dressings (containing 0.1, 0.5 and 1% MOL) on diabetic rat model. The acute dermal toxicity was carried out on healthy rats, and signs of toxicity over 14 days were observed. For wound healing studies, excision and abrasion woun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Toxicity and safety of Moringa oleifera Studies on the toxicity and safety of M. oleifera included in this review are shown in Table 3. Generally, studies on the toxic effects and safety have reported of M. oleifera to be safe in various models on mice, rats, rabbits, in vitro assays and some clinical trials (42,(58)(59)(60). In retrospect, very few toxicity and safety evaluations were encountered in investigations involving humans or clinical trials.…”
Section: Pharmacological Activities Of Moringa Oleiferamentioning
confidence: 99%
“…Toxicity and safety of Moringa oleifera Studies on the toxicity and safety of M. oleifera included in this review are shown in Table 3. Generally, studies on the toxic effects and safety have reported of M. oleifera to be safe in various models on mice, rats, rabbits, in vitro assays and some clinical trials (42,(58)(59)(60). In retrospect, very few toxicity and safety evaluations were encountered in investigations involving humans or clinical trials.…”
Section: Pharmacological Activities Of Moringa Oleiferamentioning
confidence: 99%
“…The presence of TNF-α, IL-6, and IL-1β cytokines is very vital at early phase of healing as it stimulate wound restoration [20]. According to a study by Chin et al [21], MO leaf extract film at dosage 0.1 and 0.5% successfully upregulated the production of TNF-α and IL-6 in abrasion and excision wound of diabetic Sprague Dawley rats. Whereas, at a higher concentration (50-100 μM) of VCN-2 treatment, a significant rise of pro-inflammatory cytokines level was observed in the current study ( Figures 6 and 7).…”
Section: Discussionmentioning
confidence: 99%
“…Moringa oleifera has been shown to reduce DFU wound size, improve tissue granulation, and significantly reduce the levels of a multitude of cytokines including, but not limited to, TNF-α, IL-6 and VEGF. 51 , 52 …”
Section: Current Approach To the Diabetic Foot Ulcers Managementmentioning
confidence: 99%